2006
DOI: 10.1104/pp.105.073072
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Induces the Accumulation of Superoxide via NADPH Oxidases in Arabidopsis

Abstract: Extracellular ATP can serve as a signaling agent in animal cells, and, as suggested by recent reports, may also do so in plant cells. In animal cells it induces the production of reactive oxygen species through the mediation of NADPH oxidase. Similarly, here we report that in leaves of Arabidopsis (Arabidopsis thaliana), applied ATP, but not AMP or phosphate, induces the accumulation of superoxide (O2−) in a biphasic, dose-dependent manner, with a threshold at 500 nm ATP. This effect did not require ATP hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
305
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(325 citation statements)
references
References 72 publications
12
305
1
2
Order By: Relevance
“…1A), very similar to that characterized in response to 20 mM extracellular ATP in this cell type (Demidchik et al, 2009). The concentration used is representative of wounding levels (Song et al, 2006). The increase in inwardly directed current at hyperpolarized (inside negative) voltage was observed 1 to 3 min after extracellular ADP addition (a similar time course to the extracellular ATP response reported by Demidchik et al, 2009;Shang et al, 2009) and was evident over the physiological voltage range for this cell type (Maathuis and Sanders, 1993).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…1A), very similar to that characterized in response to 20 mM extracellular ATP in this cell type (Demidchik et al, 2009). The concentration used is representative of wounding levels (Song et al, 2006). The increase in inwardly directed current at hyperpolarized (inside negative) voltage was observed 1 to 3 min after extracellular ADP addition (a similar time course to the extracellular ATP response reported by Demidchik et al, 2009;Shang et al, 2009) and was evident over the physiological voltage range for this cell type (Maathuis and Sanders, 1993).…”
supporting
confidence: 59%
“…In Arabidopsis root hairs, extracellular ATP also causes intracellular ROS accumulation by activating NADPH oxidases (Clark et al, 2010b). Leaves also support extracellular ATP-induced transcription via PM NADPH oxidases (Song et al, 2006). Nitric oxide is now also established as a product of extracellular purine nucleotide perception.…”
mentioning
confidence: 99%
“…Indeed, a number of downstream effects of P2 receptor activation, such as expression of MUC5AC, MMP-9 or IL-8 and stimulated cell migration, have been linked to activation of DUOX1 (87,105,107,108), suggesting a common association of DUOX with epithelial purinergic signaling. Intriguingly, NOX activation has similarly been associated with ATP-mediated purinergic signaling in several other mammalian cell types (160)(161)(162)(163)(164), and in NADPH oxidase-mediated wound responses in plants (165,166), which suggests that the general signaling pathway illustrated in Fig. 4 may be widely conserved as a common biological response mechanism to environmental stress.…”
Section: Mechanisms Of Duox Activation-the Presence Of Ef-hand Camentioning
confidence: 96%
“…As yet there are insufficient data to answer this question. The fact that submicromolar levels of eATP can induce signaling changes in plants (Demidchik et al, 2003;Song et al, 2006) would suggest that plants, like animals, have purinoceptors that can bind eATP with a high affinity and transduce that binding into transduction pathways. However, as discussed by Demidchik et al (2003), Roux et al (2006), and others, as yet no purinoceptor has been identified in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membrane-associated apyrases in plants could, in principle, function as ectoapyrases because plant cells, like animal cells, release significant quantities of ATP into their ECM when they are mechanically stimulated (Jeter et al, 2004), when they are wounded , and when they are engaged in activities that involve active secretion, such as growth (Kim et al, 2006). Moreover, control of this eATP could be important because plant cells have significant signaling responses to submicromolar ATP (Demidchik et al, 2003;Song et al, 2006) and extensive depletion of eATP can result in loss of cell viability (Chivasa et al, 2005).…”
mentioning
confidence: 99%